Diagnosis and Efforts to Overcome Learning Difficulties in Mathematics with Induced Fit Remedial Teaching Strategy with Participative Learning Approach - Yunita, Windha; Soedjoko, Edy; Wuryanto, Wuryanto (Unnes Journal of Mathematics Education, 2017)
Tujuan penelitian ini adalah untuk mengetahui letak dan faktor penyebab kesulitan siswa SMK kelas X dalam menyelesaikan soal program linear dan mengetahui keefektifan Induced Fit Remedial Teaching dengan pendekatan Participative Learning dalam mengatasi kesulitan belajar siswa. Penelitian ini adalah penelitian kualitatif. Pengumpulan data dilakukan dengan metode tes dan wawancara. Subjek penelitian diambil 9 dari 34 siswa kelas X Garmen 1 SMK Bina Nusantara, masing-masing 3 subjek dari kelompok atas, kelompok tengah dan kelompok bawah. Selanjutnya dilakukan wawancara terkait hasil tes diagnostik. Uji keabsahan data dilakukan dengan teknik triangulasi. Simpulan yang diperoleh (1) letak kesulitan belajar siswa adalah mengubah soal cerita ke model matematika, menentukan daerah penyelesaian dan titik pojok serta titik potong dari grafik dengan faktor penyebab kesulitan pada program linear adalah kurang memahami soal, tidak teliti, dan belum memahami langkah penyelesaian; (2) Induced Fit Remedial Teaching dengan pendekatan Participative Learning efektif mengatasi kesulitan belajar matamatika. The goal of this research is to know difficulties and factors that cause trouble for Students of SMK Grade 10 in solving linear program question, and to know the effectiveness of Induced Fit Remedial Teaching Strategy to solve the cause of students’ learning difficulties. This Reasearch is Qualitatif Research. Data collection was conducted sing Tes Method, Questionnaire and Interview. The Subjects were taken 9 from 34 students from SMK Bina Nusantara Grade 10 Garmen Class, each three subject from upper group, middle group and lower group. Then, the next step is interview related the result of diagnostic test. Test the validity of the data is done by the technique of triangulation. Conclusion obtained are (1) the cause of students’ learning difficulty is how to change the story question into math model, to determine settlement area and the corner point and and also the point of intersection of a graph. And factors that cause trouble in solving linear program question is lack of understanding of the question, not carefully and don’t understand the solution step by step (2) Effective Induced Fit Remedial Teaching Strategy with approaching Participative Learning students overcome learning difficulties.